The Impact of Compensation, Work Environment, and Job Stress on Employee Loyalty at Mirota Craft Centre: The Mediating Role of Job Satisfaction - Purnomo, Risqy Sigit; Sundjoto, Sundjoto; Rahayu, Sri; Fitrianty, Rifda (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Ensuring employees remain loyal is essential for organizational competitiveness and sustainability, more so in creative and craftsmanship-based businesses like the Mirota Craft Centre. This study explores how compensation, the work setting, and the pressures experienced by employees influence their loyalty. Job satisfaction is included as an intermediate factor to explain how these variables are linked. Using a quantitative strategy, all 125 members of the workforce participated as respondents. Questionnaire responses were analyzed through the PLS-SEM technique in SmartPLS 3.0 to test the measurement and structural models. The empirical outcomes reveal that both compensation and the overall work environment contribute positively and significantly toward enhancing satisfaction. Meanwhile, job stress exhibits a small and insignificant negative association. Satisfied employees tend to remain loyal, and satisfaction mediates the impact of compensation and workplace atmosphere on loyalty. However, stress does not operate through satisfaction to shape loyalty. The findings suggest that initiatives aimed at strengthening compensation policies and upgrading workplace quality should be prioritized to secure long-term employee attachment. Even though stress was not shown to significantly reduce satisfaction, preventive measures such as counseling services and better task distribution may still help maintain well-being. The study provides a fresh perspective by evaluating these loyalty determinants simultaneously within a single model in Indonesia’s craft industry. Expanding this research to broader contexts and incorporating other behavioral constructs is recommended.